PENGUJIAN BEBERAPA KONSENTRASI PACLOBUTRAZOL DENGAN WAKTU APLIKASI BERBEDA PADA TANAMAN TOMAT (Lycopersicum esculentum Mill.) - Indra Saputra; Nurbaiti Nurbaiti; Gunawan Tabrani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The aim of this study to improve tomato production by granting several concentrations of paclobutrazol and its application on differents time. This study was used a completely randomized factorial design 4 x 2 in three replications. The first factors was the paclobutrazol concentrate (K) in four levels (k0= No paclobutrazol, k1= 300 ppm, k2= 600 ppm and k3= 900 ppm. The second factors was the application time of paclobutrazol (A), in two levels (a1= 20th days after planting, a2= 30th days after planting). The data were analyzed using analysis of variance and mean separations with Duncan’s New Multiple Range Test at the 5% level. The result showed that there was no interaction between the paclobutrazol concentrate with the application time of paclobutrazol on variable of tomato observed. Paclobutrazol concentrate or its application time effected to plant height and number of flower. Paclobutrazol 300 ppm to 900 ppm concentrate hold up tomato plant height and reduce the number of flower. Application of paclobutrazol 20th days after planting hold up tomato plant height and reduce the number of flower. Keywords: Paclobutrazol concentrate, Different time of application, Tomato.